Pengaruh Literasi Keuangan, Inklusi Keuangan dan Financial Technology Terhadap Prilaku Keuangan pada Mahasiswa Universitas Bina Darma Palembang - Rizka Andini Nur Sabella (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of Financial Literacy, Financial Inclusion, and Financial Technology on the Financial Behavior of postgraduate students at Bina Darma University. The main problem identified is how these three variables influence students' financial management and how much they contribute to their financial behavior. The method used was a quantitative approach with data analysis using SmartPLS, involving 227 respondents. The research results show that Financial Technology has the most significant influence on Financial Behavior, with a Path Coefficient of 0.337. Financial Literacy also makes a positive contribution with a Path Coefficient of 0.258, while Financial Inclusion has a positive effect but with a smaller contribution, namely a Path Coefficient of 0.157. The R-Square value for Financial Behavior is 0.411, which indicates that the independent variables explain 41% of the variation in student Financial Behavior. The validity and reliability test of the model shows that all variables have good validity and reliability, without multicollinearity problems. This research concludes that Financial Technology and Financial Literacy play a key role in influencing Financial Behavior, while Financial Inclusion has a smaller but still significant impact. Keywords: Financial Literacy, Inclusion, Fintech, Financial Behavior